2009
DOI: 10.1016/j.jjcc.2008.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of determinations of left atrial volume by the biplane area-length and Simpson's methods using 64-slice computed tomography

Abstract: The area-length method is a simple and reproducible means of assessment of LA volume. Standardization of LA volume assessment using MSCT is important for serial follow-up and meaningful communication of results of testing among institutions and physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 18 publications
1
25
0
1
Order By: Relevance
“…In addition, similar to the work of Mahabadi et al (18), we observed excellent intra-reader agreement for all of the CMR-based methods for measuring LAV. ECG-gated 3D methods appear to provide greater agreement in LAV estimation (12). The biplane area-length and ellipse methods depend on the accurate acquisition of the respective images in order to detect the median planes perpendicular to each other, and also depend on the correct characterization of LAV during the postprocessing steps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, similar to the work of Mahabadi et al (18), we observed excellent intra-reader agreement for all of the CMR-based methods for measuring LAV. ECG-gated 3D methods appear to provide greater agreement in LAV estimation (12). The biplane area-length and ellipse methods depend on the accurate acquisition of the respective images in order to detect the median planes perpendicular to each other, and also depend on the correct characterization of LAV during the postprocessing steps.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these differences should be overcome using better software and an ECG-gated 3D method with respiratory navigator (19). In addition, in several studies of normal volunteers and patients with a sinus rhythm, it has been observed that the measurement of LAV by echocardiography underestimates the results obtained by cardiac computed tomography or MRI, which is most likely due to suboptimal limited acoustic windows of the specific study (6,7,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(24) Left atrial size and volume can be evaluated with computerised tomography (CT), usually before radiofrequency ablation of atrial fibrillation, (25) and before closure of left atrial appendage. (26) For calculation of left atrial volume CT uses echocardiographic views and methods, (27) that include area length method, Simpson's method (28) and the ellipsoid technique. (29) Other views used in CT are different from those obtained with echocardiography and CMR.…”
Section: Discussionmentioning
confidence: 99%
“…7) It is well known that the left atrial appendage (LAA) is a major cardioembolic source in patients with AF who have suffered a stroke. [8][9][10][11] We conducted a retrospective study of the relation between LAA thrombus (LAAT) and patient characteristics, transthoracic and transesophageal echocardiographic variables, and blood markers in patients with persistent AF to determine whether thrombogenesis can be predicted in patients with NVAF.…”
Section: Introductionmentioning
confidence: 99%